دراسة تغيرات تراكيز بعض العناصر الثقيلة في كل من نهر الكبير الشمالي وسد بلوران //مواقع مختارة// - كبيبو عيسى; صقر إبراهيم; عجيب شفيقة (Latakia University Journal -Biological Sciences Series, 2019)
تضمنت الدراسة إجراء تحاليل كيميائية دورية لمصدرين مائيين رئيسيين في محافظة اللاذقية وذلك بواقع ثلاث نقاط محددة لكل مصدر ،المصدر الأول هو نهر الكبير الشمالي والثاني سد بلوران (طريق البسيط). أخذت العينات على مدار عام ونصف اعتباراً من حزيران 1999 حيث تم تقدير تراكيز العناصر الثقيلة التالية: (Hg,Cd,Pb,Zn,Cu,Mn ) في نقاط الإعتيان المحددة وذلك باستخدام جهاز الامتصاص الذري (Atomic.Absorption). أوضحت النتائج بأن تراكيز العناصر الثقيلة مختلفة في المصدرين المائيين وكذلك الحال بين نقاط المواقع العائدة لنفس المصدر وذلك تبعاً لطبيعة المنطقة الجيولوجية وللفضلات والملوثات التي تصل بطريقة أو أخرى إلى المصدر المائي .وبالإستناد إلى المواصفات القياسية العالمية وتلك المعمول بها في سورية فإن مياه نهر الكبير الشمالي (النهر - البحيرة وسد بلوران (النهر-البحيرة- قناة الري) صالحة للشرب والري وذلك بالنسبة لمحتواها من العناصر الثقيلة المدروسة،ومن جهة أخرى فقد رصدنا موقعين على نهر الكبير الشمالي ،مصب النهر وكذلك الحال بالقرب من معمل البطاريات تراكيز العناصر الثقيلة أعلى من الحد المسموح به وينصح باستخدام المياه هنا للري فقط. This study includes a periodical chemical analysis of two main water sources i three chosen sites for each in Lattakia. The first source is The Northern Elkabeer river, and the second is Balloran Dam (Elbassit road ). The Samples were taken throughout 18 month starting from June 1999 . The concentration of the heavy metals (Mn, Cu, Pb, Cd and Hg ) have been determined in the definitive sites using Atomic Absorption System. The results showed variation in the concentrations of the heavy metals in both water sources, also the variations were observed among samples taken from the three sites of the same source. This variation depends on the geological aspects of the studied areas under and on the sewage and contaminants which arrive into the water sources . According to the international and, also, Syrian standards of water qualities, water of Northern Elkabeer river (the river and the lake ) and Balloran Dam (the river, the lake and the irrigation canal) can be used for human and animals need, and for plant irrigation. An excess of concentration of heavy metals was observed in water samples which were taken from Northern Elkabeer river (the river site, and close to the battary factory site ) ,and therefor water in these sites can be used only for irrigation.